Developmental phases of the age-group swimmer
Swimmers (N = 320) between the ages of 11 and 18 years were studied. A number of findings were developed, several of which reinforce previous works. 1.At a young age, faster swimmers are early or on-time maturers and, therefore, stronger and bigger. 2.High performance late maturers are likely to stay in the sport for a long time. 3.Changes in percent body fat become negligible and segment length growth stops for both males and females by the age of 16 years. 4.Before the age of 16, swimmers of both sexes experience very marked changes in physiology and anthropometric variables. 5.The greatest performance improvement for females occurs between the ages of 14 and 15 years, and for males between 15 and 16. 6.Training before 16 years of age should be primarily of a technical and base development nature (technique and aerobic endurance). 7.After 16 years of age and the establishment of a technique and aerobic base, training should stress i) anaerobic capacity and power, ii) technical racing skills, and iii) psychological skills. 8.Endurance capacity is fully developed by the age of 15 years. [In an earlier ICAR publication, the age of full development was reported as being that which coincided with puberty.] 9. Anaerobic characteristics are fully developed by 19 years of age. 10.Muscle power is fully developed by 18 years of age.